BIMBINGAN KONSELING SEBAGAI STRATEGI UNTUK MENGATASI BULLYING PADA SISWA SMP MUHAMMADIYAH 8 BENJENG – GRESIK - Paramita, Dahlia Septa; Amelasasih, Prianggi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This internship was conducted at Muhammadiyah 8 Benjeng Junior High School with the purpose of understanding and addressing bullying behaviors that occur in the school environment. During the internship program, the author applied several data collection methods, including observation, interviews, and the implementation of personal guidance and counseling sessions for students involved in bullying cases, both perpetrators and victims. The findings indicated that bullying behaviors most commonly appeared in the form of verbal teasing and social exclusion. These behaviors were influenced by several factors, such as a lack of empathy, differences in individual character, and the strong influence of peer groups. Through a personal guidance and counseling approach, students were guided to recognize the negative psychological and social impacts of bullying, develop positive social skills, and enhance mutual respect among peers. The counseling process encouraged students to reflect on their attitudes and behaviors, ultimately supporting positive behavioral change. This internship provided the author with valuable practical experience in applying guidance and counseling theories in a real school setting. Furthermore, the internship contributed to increasing awareness of the essential role of guidance and counseling services in fostering a safe, supportive, and empathetic school environment for all students.